Microstructure and creep behaviour of pressure boundary welds from Grade 91 steel tee. (May 2014) - Parker, J.; Weiss, W.
Abstract : New power generation equipment firing either coal or natural gas is required to operate at high levels of efficiency with greater operational flexibility than has been true for such equipment in the past. Because of their unique combination of superior creep strength and favourable thermal–physical properties, Grade 91 and the other creep strength enhanced ferritic (CSEF) steels are materials of choice for components operating in the elevated temperature sections of this equipment. To fully realise the benefits of these alloys, it is essential that careful control be maintained during all phases of processing of the material, from design, through material production, to fabrication and installation. Absent such control, rates of damage accumulation can be much greater than expected from 'Code' minimum data. Problems have been associated with incorrect heat treatment: failure to develop the necessary structure during the normalising heat treatment or breakdown of that structure during subsequent sub-critical heat treatments. Heat treating schedules must consider not only the specific chemical composition of the base and weld filler metal, but also the cumulative impact of multiple heat treatments on the final material structure and its properties. The present work has examined the performance of welds in an ex-service component. The results suggest that, even when less than optimal heat treatment is carried out, the susceptibility for Type IV cracking in weld heat affected zones may be the life limiting factor for most CSEF steel components.